ABA-induced alternative splicing drives transcriptomic reprogramming for drought tolerance in barley - Anna Collin; Hubert Matkowski; Ewa Sybilska; Asmarany Biantari; Oliwia Król; Agata Daszkowska-Golec (BMC Plant Biology)
Abstract Background Abscisic acid (ABA) is a phytohormone that mediates plant responses to drought stress by regulating stomatal conductance, gene expression, and photosynthetic efficiency. Although ABA-induced stress priming has shown the potential to improve drought tolerance, the molecular mechanisms underlying ABA pretreatment effects remain poorly understood. This study aimed to determine how ABA pre-treatment at the booting stage influences physiological and molecular responses to drought at the heading stage in barley. Results The ABA-treated plants exhibited earlier stomatal closure, increased expression of ABA-responsive genes (HvNCED1, HvBG8, and HvA22), and maintained higher chlorophyll levels under drought conditions. Photosynthetic parameters, including photosystem II activity, electron transport rate, and the number of active reaction centers, were preserved in ABA-pretreated plants compared with drought-only plants. Transcriptomic analysis revealed that ABA pre-treatment primed plants for faster activation of stress-responsive pathways, with enhanced expression of genes related to chromatin modifications, RNA metabolism, and ABA signaling during drought. Importantly, Alternative splicing (AS) and isoform switching were significantly amplified in ABA-pretreated plants, underscoring a unique molecular mechanism of ABA priming that enhances drought resilience. Post-stress recovery analysis revealed a greater number of differentially expressed genes (DEGs) and alternatively spliced transcripts (DAS) in ABA-pretreated plants, particularly those involved in chromatin organization and photosynthesis. Physiological analyses demonstrated that time- and dose-optimized ABA applications improved yield parameters, including grain weight and seed area, while mitigating spike sterility under drought conditions. Conclusions This study demonstrates that ABA pretreatment enhances drought resilience in barley by triggering early stomatal closure, preserving chlorophyll content, and maintaining photosynthetic performance under water stress. At the molecular level, ABA priming accelerates stress-response pathways, promoting alternative splicing, isoform switching, and chromatin modifications that enable transcriptome plasticity. These processes facilitate faster recovery and sustain critical yield components, such as spike number and grain weight, when ABA is applied at optimized timing and concentrations. While large-scale ABA application poses challenges, this study provides a framework for breeding and agronomic strategies to mimic ABA effects, offering a practical path to enhance drought tolerance and yield stability in barley.